(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
«The sulphurous actress», «L’enfant perdue du cinéma», «The woman of “Last tango”»: this is how the media defined Maria Schneider, the French actress who gained international renown for her performance in “Last tango in Paris” at the age of 19. The role, written by Bernardo Bertolucci, undoubtedly marked Schneider’s image and turned this fresh young woman into an icon of rebellious free love (“Cari genitori”) and the symbol of female emancipation (“Io sono mia”). During her meteoric passage through European stardom, Schneider also scandalized Italy’s conservative society. This article focuses not only on the actress’s “persona”, but also on the reception of Schneider’s sexual life in the Italian press, where she was compared to Juliette Lorsange, De Sade’s nymphomaniac character.